Conventional Kinesin Mediates Microtubule-Microtubule Interactions In Vivo - Straube, Anne (The American Society for Cell Biology, 2006)
Conventional kinesin is a ubiquitous organelle transporter that moves cargo toward the plus-ends of microtubules. In addition, several in vitro studies indicated a role of conventional kinesin in cross-bridging and sliding microtubules, but in vivo evidence for such a role is missing. In this study, we show that conventional kinesin mediates microtubule-microtubule interactions in the model fungus Ustilago maydis. Live cell imaging and ultrastructural analysis of various mutants in Kin1 revealed that this kinesin-1 motor is required for efficient microtubule bundling and participates in microtubule bending in vivo. High levels of Kin1 led to increased microtubule bending, whereas a rigor-mutation in the motor head suppressed all microtubule motility and promoted strong microtubule bundling, indicating that kinesin can form cross-bridges between microtubules in living cells. This effect required a conserved region in the C terminus of Kin1, which was shown to bind microtubules in vitro. In addition, a fusion protein of yellow fluorescent protein and the Kin1tail localized to microtubule bundles, further supporting the idea that a conserved microtubule binding activity in the tail of conventional kinesins mediates microtubule-microtubule interactions in vivo.